Controllability and observability of technological control objects - Луцька, Н.М.; Савченко, Т.В. (Eastern-European Journal of Enterprise Technologies, 2012)
Basic principles of observable and controllability of technological control objects are resulted. This question is probed on an example of pasteurization-cool settings of suckling production which is described by four linear differential equations.